Hubungan Minat Tehadap Jurusan dengan Perencanaan Karir Siswa Sekolah Menengah Kejuruan - Verly Syafitri, Intan; Daharnis; Ifdil (Risâlah Jurnal Pendidikan dan Studi Islam, 2026)
The relationship between interests and majors is an important factor that influences vocational high school students’ career planning. Currently, you can find many students who change majors because they follow their friends in choosing a major. So students are confused in planning their careers. Career planning is a complex process that involves various factors, including interest in your major and self-confidence. Interest in a major is a person’s interest in a particular field of study or work. Self-confidence is a person’s belief in his ability to achieve his goals. Factors that influence students’ career planning are internal factors and external factors. As efforts continue to be made to improve the quality of vocational schools through revitalization movements throughout Indonesia, the determining factors that have a greater role are internal factors originating from the students themselves. Interest in majors is one of the internal factors within students which is seen to have a strong relationship with increasing students’ career planning abilities. Interest in a major is very important for a student’s future, therefore choosing a major must be done carefully, so that the wrong major does not occur. The current trend is that many students are not interested in majoring and this can lead to bad things after graduating. Bad consequences occurred after that, namely reluctance to study and according to him the quality and academic achievement was because students felt they were wrong in choosing a major.